2010
DOI: 10.1021/cg100322p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Impurity on Diamond Crystal Growth Processes

Abstract: In this paper, we report on the influence of nitrogen concentration in metal melts on the growth processes, morphology, and defect-and-impurity structure of diamond crystals. In two series of experiments, the concentration of nitrogen in the growth system was varied by adding Fe 3 N and CaCN 2 to the charge; the other parameters and conditions of the growth were constant: FeNiC system, P = 5.5 GPa, T = 1400 °C, and duration of 65 h. It has been found that, with increasing nitrogen concentration (C N ) in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(111 citation statements)
references
References 28 publications
4
104
0
Order By: Relevance
“…In addition to the temperature, the concentration of nitrogen plays important role in crystallization of different carbon phases (diamond and graphite). Recent experiments performed by Palyanov et al (2010) in a Fe-Ni-C system within the diamond stability field demonstrated that, with increasing concentration of nitrogen, the growth of a single crystal diamond is followed by formation of block twinned crystals, increasing of density of dislocations (like in our sample) and then by crystallization of metastable graphite. This explains the existence of the association: graphite + diamond + "chalypite" + cohenite + native iron (some of these phases may be metastable); the latter exists, in metallurgical solidus systems, as austenite (-Fe).…”
Section: Thermodynamic Conditions Of Iron Carbide and Graphite Formatmentioning
confidence: 55%
“…In addition to the temperature, the concentration of nitrogen plays important role in crystallization of different carbon phases (diamond and graphite). Recent experiments performed by Palyanov et al (2010) in a Fe-Ni-C system within the diamond stability field demonstrated that, with increasing concentration of nitrogen, the growth of a single crystal diamond is followed by formation of block twinned crystals, increasing of density of dislocations (like in our sample) and then by crystallization of metastable graphite. This explains the existence of the association: graphite + diamond + "chalypite" + cohenite + native iron (some of these phases may be metastable); the latter exists, in metallurgical solidus systems, as austenite (-Fe).…”
Section: Thermodynamic Conditions Of Iron Carbide and Graphite Formatmentioning
confidence: 55%
“…Detailed SIMS traverses across growth sectors in synthetic diamonds from a metal-carbon system reveal the same distribution of nitrogen between {111} and {100} sectors [5]. Furthermore, sectors of octahedra show nitrogen abundances, which are close to that of the starting graphite [5,17]. Significant nitrogen depletion in cube sectors in comparison to nitrogen content in initial graphite documents the incompatible behavior of nitrogen in the 100 sector of diamond.…”
Section: Fractionation Of Nitrogenmentioning
confidence: 80%
“…Such coordinated groups will have characteristics favouring their incorporation in a particular crystal structure: Composition of the solvent and solvent impurities will also influence the stability of particular coordinated groups of atoms. For example, an increasing abundance of nitrogen impurity in a diamond-producing metal-carbon melt will favour to crystallization of graphite instead of diamond [17].…”
Section: Crystal Structure Characteristics and General Regularities Omentioning
confidence: 99%
“…A PtRh6/PtRh30 thermocouple (Krastsvetmet, Krasnoyarsk, Russia) was used in each experiment for the temperature measurements. Given the data of calibration experiments [26,27], the accuracy of temperature and pressure measurements was ±40 • C and ±0.2 GPa, respectively. The high-pressure cell and sample assemblies were the same in all experiments of this series and was similar to that used in our previous studies of the Mg-C system [11,12].…”
Section: Methodsmentioning
confidence: 99%